Singularities in the profession of teaching: experiences of a teacher (Olhar de Professor, 2025)
In this study, we aim to understand the teaching profession through the narrative of Valesca, a primary school teacher who shares her life story, profession, and significant experiences. We chose the narrative (auto)biographical research approach because it allows us to delve into the cognitive, affective, and action-oriented dimensions that the subject/narrator selects and organizes from their life and professional history to share with other teachers. Our dialogue is grounded in the works of key authors in the field of narrative (auto)biographical research, particularly Bolívar (1995, 1999, 2002, 2012, 2016); Ricoeur (1995); and Bruner (1988). We identified several educational policies that constrain teachers' pedagogical practices in Brazil. However, Valesca does not fully comply with these directives in her teaching. Instead, she seeks to address the specific needs of her students, adapting her teaching practices according to the material conditions, the context of her school, and her personal and professional experiences. These choices can positively impact pedagogical autonomy, foster innovation in teaching practices, encourage collaborative engagement, and resist ideological pressures. Conversely, they may lead to curricular misalignment, educational inequality, lack of monitoring and assessment, as well as the isolation and fragmentation of knowledge. This stance of teaching outside official guidelines, while creating room for more inclusive and contextual practices, may also result in imbalances in access to quality education and hinder the construction of a solid foundation for students within a cohesive national system.
Keywords: Narrative; (Auto)biography; Teaching profession; Pedagogical practice